Mitochondrial Ca2+ influx targets cardiolipin to disintegrate respiratory chain complex II for cell death induction - Hwang, M-S; Schwall, C T; Pazarentzos, E; Datler, C; Alder, N N; Grimm, S (Cell death and differentiation, 2014)
Massive Ca 2+ influx into mitochondria is critically involved in cell death induction but it is unknown how this activates the organelle for cell destruction. Using multiple approaches including subcellular fractionation, FRET in intact cells, and in vitro reconstitutions, we show that mitochondrial Ca 2+ influx prompts complex II of the respiratory chain to disintegrate, thereby releasing an enzymatically competent sub-complex that generates excessive reactive oxygen species (ROS) for cell death induction. This Ca 2+ -dependent dissociation of complex II is also observed in model membrane systems, but not when cardiolipin is replaced with a lipid devoid of Ca 2+ binding. Cardiolipin is known to associate with complex II and upon Ca 2+ binding coalesces into separate homotypic clusters. When complex II is deprived of this lipid, it disintegrates for ROS formation and cell death. Our results reveal Ca 2+ binding to cardiolipin for complex II disintegration as a pivotal step for oxidative stress and cell death induction.